PELAKSANAAN SANKSI ADMINISTRASI PAJAK YANG DIJATUHKAN TERHADAP PENGUSAHA KENA PAJAK YANG BELUM MENYELESAIKAN PEMBAYARAN PAJAK. - Aditya Saputra (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT To determine and implement administrative sanctions against employers who commit offences taxable i.e. by having SUCH control card (the notice) the payment of the VAT. With a look of such supervision and payment card the VAT, held eksaminasi i.e. researching a single receipt of SPM (the notice period) and then separates the timely report SPM and SPM report late.If a taxable entrepreneur did not carry out his obligations properly,then as the construction of the directorate general of taxation will issue some form of administrative sanction, either in the form interest, fines or ascension. On the issue of the legal consequences of sanctions implementation, then the question will be to how far the influence of administrative sanctions against employers taxable in performing the duty of taxation . Based on the data that can be run during auto summary research author turns out situations and conditionshave enabling employers taxable left well enough alone in carrying out its oligations in accordance with a system of self just my assessment. This is due to the awareness of employers still felt less taxable and still need guidance and coaching from the directorate general of taxes regularly and continuosly.